HUBUNGAN ANTARA LAMA PEMAKAIAN KB IUD DENGAN KEJADIAN LEUKORRHEA DI WILAYAH KERJA PUSKESMAS BADES KECAMATAN PASIRIAN KABUPATEN LUMAJANG - IIN LIASASI; NOVA HIKMAWATI; SRI WAHYUNINGSIH (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
IUD (Intra Uterine Device) is a contraceptive made of plastic that has a shape like the letter 'T' and is placed in the uterus to prevent pregnancy. At 3 months after installation there were complaints of Leukorrhea. Leukorrhea is discharge other than blood from the vaginal canal that is out of the ordinary, whether it smells or not, and is accompanied by itching or burning. The purpose of this study was to analyze the correlation between the duration of IUD use and the incidence of leukorrhea in the Bades Community Health Center, Pasirian, Lumajang. The research method used is an analytic observational research method with a cross-sectional approach. The Sampling used simple random sampling, the number of samples was 30 respondents. The research instrument used a questionnaire. The results showed that the majority of women who had used IUDs for > 3 months experienced physiological leukorrhea (56,7%). Statistical test results using Chi-Square with α = 5%, the results obtained p value = 0.013 <0.05. From these results, it can be stated that there is a significant correlation between the duration of IUD use and the incidence of leukorrhea in the Working Area of ​​the Bades Health Center, Pasirian, Lumajang. Mothers or family planning acceptors are better off adding information or knowledge about IUD family planning so that they can find out the side effects that can occur from using IUD family planning. In addition, health workers, especially midwives, also remain vigilant in providing services, especially regarding family planning, and must pay attention to the impact that will appear on the acceptor. If something is detrimental to the patient, then find the right solution. It can be a useful reference for further research related to the duration of IUD use and the incidence of leukorrhea.